Inflation and Balanced-Path Growth with Alternative Payment Mechanisms - Max Gillman; Michal Kejak (Hungarian Academy of Sciences, Institute of Economics, 2004)
The paper shows that contrary to conventional wisdom an endogenous growth economy with human capital and alternative payment mechanisms can robustly explain major facets of the long run inflation experience. A negative inflation-growth relation is explained, including a striking nonlinearity found re-peatedly in empirical studies. A set of Tobin (1965) effects are also explained and, further, linked in magnitude to the growth effects through the interest elasticity of money demand. Undis-closed previously, this link helps fill out the intuition of how the inflation experience can be plausibly explained in a robust fashion with a model extended to include credit as a payment mechanism.
Keywords: O42; E31; E22; 330; Human capital; cash-in-advance; interest-elasticity; credit production